ANALISIS PENGETAHUAN DAN SIKAP SISWA PADA MATERI JAMUR - Novita Ercahaya Simanjuntak; Hasruddin Hasruddin (Jurnal Pelita Pendidikan, 2016)
This research was conducted to know the knowledge and attitudes of students about Fungus class XSMA Negeri 1 Tarutung on 2015/2016 academic year. Types of research used in this research is descriptive. Thepopulation of this research is all of student class X Semester I SMA Negeri 1 Tarutung that is consists of eightclasses. The sample of this research was taken into two class that is class X1 and class X3 that the both of itconsist 35 person. The technique which is used to take the sample with “Cluster Random Sampling”. Datacollection instrument was cognitive test sheet consist 40 question that has been validated by validator andthen are given to know the validity, reliability, and difficulty level test. To known the attitude of students isused the questionnaire of attitudes consist 40 question about Fungus. The result of the research show that thehigh mastery knowledge of students categorized at indicator 7 about concluding the role of fungus in daily lifewas 86.12% and the low mastery knowledge of students categorized at indicator 2 about describing thedifferences of each fungus was 34.28%. The result from questionnaire show that the high mastery attitude ofstudents categorized at indicator 1 about express gratitude to God was 91.42% and the low mastery attitude ofstudents categorized at indicator 4 about convey the idea, inform, and argument was 64.57%. The result ofresearch also show that the correlation between knowledge and attitudes of students about Fungus was 0.789(high), and the contribution was 62%.Keyword: Knowledge, Attitude, Fungus